Current status and challenges in timely detection of cervical cancer in Mexico: expert consensus - Barquet-Muñoz, Salim Abraham; Arteaga-Gómez, Cristina; Díaz-López, Elsa; Rodríguez-Trejo, Amelia; Marquez-Acosta, Janeth; Aranda-Flores, Carlos (Frontiers in Oncology, 2024)
Cervical cancer is a significant public health problem in low- and middle-income countries, accounting for 85% of new cases worldwide. Due to poorly organized screening programs, cervical cancer is more likely to develop in vulnerable groups who do not initiate or rarely undergo screening. Cervical cytology and detecting high-risk human papillomavirus types are the recommended screening tools. Further, these strategies allow for accurately identifying women at a higher risk of cervical cancer and establishing screening times. New detection tools, such as novel biomarkers or automatic HPV detection in the vagina or urine, can improve screening coverage. This review aims to identify the challenges faced by detection programs and screening tools in Mexico to provide evidence-based recommendations to improve early detection programs for cervical cancer.